A comprehensive comparison between non-bulking and bulking aerobic granular sludge in microbial communities. (December 2019) - He, Qiulai; Zhang, Jing; Gao, Shuxian; Chen, Li; Lyu, Wanlin; Zhang, Wei; Song, Jianyang; Hu, Xiaoling; Chen, Rongfan; Wang, Hongyu; Yu, Jian
Graphical abstract: Highlights: Comprehensive comparisons of non-bulking and bulking granules were profiled. EPS mattered during filamentous bulking and maintenance. Biocide H2 O2 (1‰, v/v) was used as the non-specific method for controlling bulking. Overgrowth and suppression of filaments Singulisphaera and Thiothrix were decisive. Abstract: Filamentous sludge bulking poses great threats to operational stability of aerobic granular sludge. Exploration of the microbial community aids knowledge of the causative factors to sludge bulking and guides directions for corresponding actions for prevention and controlling. Detailed changes of bacterial community within the non-bulking and bulking were performed and compared with a non-specific method through 1‰ (v/v) hydrogen peroxide (H2 O2 ) addition. Results revealed that non-bulking/bulking granules maintained effective carbon and nitrogen removal, while bulking completely deteriorated enhanced biological phosphorus removal (EBPR). Excess extracellular polymeric substances (EPS) especially polysaccharide (PS) were directly linked with sludge bulking and abundant PS contributed to subsequent granular re-stability. Filamentous bulking dramatically altered the bacterial populations and 1‰ H2 O2 effectively controlled bulking by eliminating causative filaments Singulisphaera and Thiothrix . Together, this study provides new insights into the non-bulking/bulking granules and could direct the prevention and control of filamentous bulking in aerobic granules.